Implementation of 3M Activities for Children's Fine Motor Development at Muslimat NU I Kindergarten, Pamekasan - Noer Cholis; Mediyana; Dewi Pusparini (STIT Attaqwa, 2025)
This study aims to determine how the 3M activities (drawing, tearing, and sticking) can develop fine motor skills in early childhood at Muslimat NU I Kindergarten in Pamekasan. The method used was a descriptive qualitative approach, with the research subjects consisting of teachers and children in Group A (aged 4-5 years). Data were collected through observation, interviews, and documentation. The results showed that the 3M activities can improve hand-eye coordination, concentration, and creativity in children. This activity was implemented in three stages: planning, implementation, and evaluation, and has been proven to have a positive impact on children's fine motor development.